Sequence diversity within the HA-1 gene as detected by melting temperature assay without oligonucleotide probes - Mattiuz Pier; Malentacchi Cecilia; Giorgi Massimo; Graziano Claudio; Porfirio Berardino (BMC Medical Genetics, 2005)
Abstract Background The minor histocompatibility antigens (mHags) are self-peptides derived from common cellular proteins and presented by MHC class I and II molecules. Disparities in mHags are a potential risk for the development of graft-versus-host disease (GvHD) in the recipients of bone marrow from HLA-identical donors. Two alleles have been identified in the mHag HA-1. The correlation between mismatches of the mHag HA-1 and GvHD has been suggested and methods to facilitate large-scale testing were afterwards developed. Methods We used sequence specific primer (SSP) PCR and direct sequencing to detect HA-1 gene polymorphisms in a sample of 131 unrelated Italian subjects. We then set up a novel melting temperature (Tm) assay that may help identification of HA-1 alleles without oligonucleotide probes. Results We report the frequencies of HA-1 alleles in the Italian population and the presence of an intronic 5 base-pair deletion associated with the immunogeneic allele HA-1H. We also detected novel variable sites with respect to the consensus sequence of HA-1 locus. Even though recombination/gene conversion events are documented, there is considerable linkage disequilibrium in the data. The gametic associations between HA-1R/H alleles and the intronic 5-bp ins/del polymorphism prompted us to try the Tm analysis with SYBR® Green I. We show that the addition of dimethylsulfoxide (DMSO) during the assay yields distinct patterns when amplicons from HA-1H homozygotes, HA-1R homozygotes, and heterozygotes are analysed. Conclusion The possibility to use SYBR® Green I to detect Tm differences between allelic variants is attractive but requires great caution. We succeeded in allele discrimination of the HA-1 locus using a relatively short (101 bp) amplicon, only in the presence of DMSO. We believe that, at least in certain assets, Tm assays may benefit by the addition of DMSO or other agents affecting DNA strand conformation and stability.